The Respon Pertumbuhan Varietas Bibit Pepaya (Carica papaya L.) Pada Perlakuan Lama Perendaman Auksin Yang Berbeda: Respon Pertumbuhan Varietas Bibit Pepaya (Carica papaya L.) Pada Perlakuan Lama Perendaman Auksin Yang Berbeda - Yushi Mardiana; Eka Putri Setyaningsih; Widyana Rahmatika (JURNAL ILMIAH AGRINECA, 2026)
Papaya (Carica papaya L.) is an important horticultural crop, and seedling quality greatly determines its growth and productivity. The application of auxin through seed soaking is expected to enhance germination and seedling development. This study aimed to evaluate the effect of different papaya varieties and auxin soaking durations on germination and early seedling growth. The experiment was conducted from March to May 2025 in Pranggang Village, Kediri Regency, East Java, using a factorial randomized block design (RBD). The first factor was papaya variety (California and Bangkok), and the second factor was auxin soaking duration at four levels (6, 12, 18, and 24 hours). Ten treatment combinations were obtained, each replicated three times with six plants per replication. The results showed a significant interaction between papaya variety and auxin soaking duration. The best interaction was observed in the California variety soaked for 12 hours, producing an average of 15.53 leaves at 35 days after sowing (DAS). However, the Bangkok variety showed superior performance overall, with the highest values in most observed variables. Auxin soaking for 12 and 18 hours provided the most favorable effect on seedling growth, as indicated by the highest mean values across most parameters, except for germination rate. The Bangkok papaya variety demonstrated the best overall growth performance, while auxin soaking for 12–18 hours was the most effective treatment for enhancing seedling development. These findings provide practical insights for improving papaya seedling quality and optimizing early growth.